Effects of Egg White Addition on Moisture, Protein Content, Solubility and Hedonic Quality of Foam-mat Dried Soybean Powder - Priska Tiara Primastuti; Antonius Hintono; Inish Chris P. Mesias; Yoga Pratama (Diponegoro University, 2024)
Soymilk is a widely popular beverage and often regarded as a dairy alternative. One option to increase the shelf life of soymilk is by converting it into soy milk powder. Foam mat drying technique offers faster drying process due to larger surface area and better rehydration due to more porous agglomerates. This research aims to determine the effects of egg white addition as a foaming agent in the foam-mat drying process of powdered soymilk on the water content, protein, solubility and hedonic quality. The research employed a completely randomized design with 4 treatments and 5 replications, i.e., addition of egg white as a foaming agent at different concentrations: 25%, 30%, 35%, and 40% (w/v). The results showed that the increasing egg white concentration significantly increases protein content and reduces both solubility and hedonic quality of the powdered soymilk product. However, egg white addition has no significant effect on water content. The best powdered soymilk product was observed at 25% egg white addition, which gave a water content of 3.88%, protein content of 23.61%, and solubility of 61.06%.